Efektifitas Strategi Pelayanan Pastoral Konseling Kepada Pasien Panti Rehabilitasi Narkoba - Linda Zenita Simanjuntak; Malik Malik; Hasahatan Hutahaean (Evangelikal: Jurnal Teologi Injili dan Pembinaan Warga Jemaat, 2021)
The number of young people who fall into the trafficking of drugs is increasing. The phenomenon of the number of prisons and detention centers inhabited by people assisted by drug cases is no longer a secret. It is not uncommon for church youth to be counted on that number so that components of the Church such as pastors, assemblies, service activists, and other elements of society deserve to give a more serious portion of attention. Because the face of the future church cannot be separated from the Church Youth today. This research departs from this fact and the services of North Sumatra STT students at the Rehabilitation Center in Medan. More than fifteen years of experience in this area is worth exploring through field research. The method used is qualitative and with 28 people who are the objects of research from the Rehabilitation Center. Data were obtained from students who actively carry out mentoring services to Rehabilitation Institutions, Rehabilitation Institution Managers, and patient families from some of the objects (patients). The results show that there are five steps; understanding the counselee, giving loving help, the role of a father, and family prayer, provides a better change despite the variety of outcomes (cures) of people who have participated in the rehabilitation program. Pastoral care and the care of family or parents add to the healing process. This has something to do with spirituality and the pattern of pastoral Christian counseling services provided. But on the other hand, the formation of habits in serving students of the Theological College (STT) needs to be pursued through pastoral counseling services with assistance to people who are addicted and follow rehabilitation programs. ABSTRAKKaum muda yang terjerumus kepada penyalahgunaan narkoba dan obat-obatan semakin bertambah. Fenomena banyaknya Lapas dan Rutan dihuni oleh warga binaan kasus narkoba bukan rahasia lagi. Tidak jarang pula pemuda gereja yang terhitung pada bilangan itu sehingga komponen Gereja seperti pendeta, majelis, aktifis pelayanan dan elemen masyarakat lainnya patut untuk memberi porsi perhatian yang lebih serius. Sebab wajah gereja masa depan tidak terlepas dari Pemuda Gereja masa kini. Penelitian ini berangkat dari fakta tersebut dan pelayanan mahasiswa STT Sumatera Utara di Panti Rehabilitasi di Medan. Pengalaman lebih lima belas tahun pada bidang ini patut untuk ditelusuri melalui penelitian lapangan. Metode yang digunakan adalah kualitatif dan dengan 28 orang yang menjadi objek penelitian dari Panti Rehabilitasi. Data diperoleh dari mahasiswa yang aktif melaksanakan pelayanan pendampingan ke Panti Rehabilitasi, Pengelolah Panti Rehabilitasi dan keluarga pasien dari sebagian objek (pasien). Hasilnya menunjukkan adanya lima langkah; memahami konseli, memberi pertolongan penuh kasih, peran Ayah, dan doa keluarga, memberikan perubahan yang lebih baik meski adanya keragaman outcome (kesembuhan) dari orang-orang yang pernah mengikuti program rehabilitasi tersebut. Pendampingan pastoral dan perhatian keluarga atau orang tua menambah daya proses penyembuhan. Hal ini ada sangkut pautnya dengan spiritualitas dan pola pelayanan pastoral konseling Kristen yang diberikan. Namun di sisi lain pembentukan kebiasaan dalam melayani bagi mahasiswa Sekolah Tinggi Teologi (STT) perlu diupayakan melalui pelayanan pastoral konseling dengan pendampingan kepada orang-orang yang kecanduan dan mengikuti program rehabilitasi.